Measurement of machining forces and surface roughness in turning of AISI 304 steel using alumina-MWCNT hybrid nanoparticles enriched cutting fluid. (January 2020) - Kumar Sharma, Anuj; Kumar Tiwari, Arun; Rai Dixit, Amit; Kumar Singh, Rabesh
Graphical abstract: Highlights: Hybridization of alumina and MWCNT in a fixed proportion of 90:10. Thermophysical properties characterization of hybrid nanofluids. Wettability and tribology testing of hybrid nanofluids. Performance analysis of hybrid nanofluid on turning operation. Abstract: Researchers so far have given more attention to the performance of mono type nanoparticle enriched cutting fluids in machining. In present investigation, a hybrid nano-cutting fluid has been developed by mixing alumina based cutting fluid with multi walled carbon nano tube (MWCNT) nanoparticles in different volumetric concentrations of 0.25, 0.75 and 1.25 vol%. The prepared hybrid and base (Alumina nanofluid) nanofluids were tested for their thermophysical properties. Furthermore, pin on disc test and contact angle measurement of all the nanofluid samples were performed to understand their tribological behaviour and spreadability, respectively. The results revealed that the increase of nanoparticle concentration in cutting fluid reduced the wear and the lowest wear was observed with hybrid nanofluid. Later their performances as a cutting fluid by using minimum quantity lubrication (MQL) technique has been evaluated during turning of AISI 304 steel in the terms of machining forces and surface roughness and regression models have been developed for machining forces and surface roughness. The results clearly establish that the performance of hybrid nanofluid is found to be significantly better compare to alumina nanoparticle mixed cutting fluid.